AI-powered smart assistants: Your key to self-learning success - Praherdhiono, Henry; Jamaludin, Jamaludin; Kurniawan, Citra; Afriani, Afriani; Dhini, Bachriah Fatwa; Sumarno, Alim; Kristanto, Andi; Pinandito, Aryo (Psychology, Evaluation, and Technology in Educational Research, 2024)
This research aims to develop a prototype of a smart assistant system for independent learning activities based on Artificial Intelligence. Web-based instructional design (WBID) approach is used in research to develop intelligent assistant systems. Artificial Intelligence-Learning Analytics helps students make important decisions and creates an effective and efficient learning environment while still building learning independence. The method used is a research and development (R&D) approach. The findings of this research are an intelligent assistant system in independent learning activities assisted by artificial intelligence in the form of the AILA ChatBot application. In the end, this research concludes that the ChatBOT application developed in this research is used to provide recommendations for using AI applications to students, which are then implemented and integrated into SPOC/MOOC.